SHM_120677_HST_3D Ceramic Jug - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a ceramic jug from the Middle Ages, collected in the field from Slottsfjärden in Kalmar and currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=663

Link to Sök I Samlingarna

https://samlingar.shm.se/object/D5993B28-ABE7-4C7A-839F-ABFB56394FFF
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; Swedish Middle Ages; Slottsfjärden; History and archaeology; Archaeology/history; Dynamic Collections; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi